Training Vocational High School Students in Audio-Based Multimedia to Support English Language Learning - Asti Gumartifa; Bengawan Alfaresi; Astri Puspita Sari (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: In the 21st-century educational context, integrating digital literacy and multimedia is essential for both students and teachers. However, vocational school students, particularly those at SMK Muhammadiyah 2 Palembang, face significant challenges in effectively utilizing audio-based multimedia tools to support their learning process.Aims: This community service activity aims to enhance students’ ability to apply audio media effectively, thereby improving the quality and engagement of the learning process. The focus is on equipping students with practical skills that foster deeper and more interactive learning experiences through audio-based media.Methods: The approach used in this activity was hands-on practice supported by qualitative data collection. The training took the form of a workshop, involving 21 second-grade students of SMK Muhammadiyah 2 Palembang. In addition to demonstrations, direct practice sessions were conducted, emphasizing the use, implementation, and integration of audio media in learning. A Likert-scale questionnaire consisting of 18 indicators across four assessment areas was used to evaluate the activity’s effectiveness.Results: Quantitative data analysis shows high levels of participant satisfaction, with most responses categorized as